2017
DOI: 10.1182/blood-2017-02-768176
|View full text |Cite
|
Sign up to set email alerts
|

Cellubrevin/vesicle-associated membrane protein-3–mediated endocytosis and trafficking regulate platelet functions

Abstract: Endocytosis is key to fibrinogen (Fg) uptake, trafficking of integrins (αIIbβ, αβ), and purinergic receptors (P2Y, P2Y), and thus normal platelet function. However, the molecular machinery required and possible trafficking routes are still ill-defined. To further identify elements of the platelet endocytic machinery, we examined the role of a vesicle-residing, soluble -ethylmaleimide factor attachment protein receptor (v-SNARE) called cellubrevin/vesicle-associated membrane protein-3 (VAMP-3) in platelet funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Very little is known about the difference between the two Rab8 isoforms, although it is postulated that they function in both distinct and overlapping compartments in various cell types (Chen, Liang, Chia, Ngsee, & Ting, 2001;Sato et al, 2014 (Figures 2c and 4c). We also found that depletion of VAMP3, a downstream regulator fusion event controlled by both Rab8b and Rab11b, could result in an increased number of intact vacuoles harbouring the ΔsdhA strain (Figure 5c) (Banerjee et al, 2017;Finetti et al, 2015;Wilcke et al, 2000). VAMP3 is SNARE protein that drives membrane fusion, thus pointing to a model in which disruption of membrane integrity is a consequence of fusion with a compartment that destabilises the LCV (Hu, Hardee, & Minnear, 2007).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Very little is known about the difference between the two Rab8 isoforms, although it is postulated that they function in both distinct and overlapping compartments in various cell types (Chen, Liang, Chia, Ngsee, & Ting, 2001;Sato et al, 2014 (Figures 2c and 4c). We also found that depletion of VAMP3, a downstream regulator fusion event controlled by both Rab8b and Rab11b, could result in an increased number of intact vacuoles harbouring the ΔsdhA strain (Figure 5c) (Banerjee et al, 2017;Finetti et al, 2015;Wilcke et al, 2000). VAMP3 is SNARE protein that drives membrane fusion, thus pointing to a model in which disruption of membrane integrity is a consequence of fusion with a compartment that destabilises the LCV (Hu, Hardee, & Minnear, 2007).…”
Section: Discussionmentioning
confidence: 66%
“…We demonstrated that depletion of the Rab5 effector EEA1 and the Rab11b effector Rab11FIP1 partially restored integrity of the ΔsdhA‐ containing vacuole and increased intracellular growth of the mutant, generating phenotypes indistinguishable from depletion of the GTPases (Figures c and c). We also found that depletion of VAMP3, a downstream regulator fusion event controlled by both Rab8b and Rab11b, could result in an increased number of intact vacuoles harbouring the ΔsdhA strain (Figure c) (Banerjee et al, ; Finetti et al, ; Wilcke et al, ). VAMP3 is SNARE protein that drives membrane fusion, thus pointing to a model in which disruption of membrane integrity is a consequence of fusion with a compartment that destabilises the LCV (Hu, Hardee, & Minnear, ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…1 P latelet activation depends upon exocytosis, a process that involves platelet granules releasing their prothrombotic contents into the blood. Banerjee and colleagues now show that platelets rely on endocytosis as well.…”
Section: Charles J Lowenstein University Of Rochester School Of Medimentioning
confidence: 99%